2014
DOI: 10.1080/14635240.2014.893138
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of osteoporosis health beliefs based on the health belief model

Abstract: Osteoporosis health beliefs are components of theoretical models that predict changes in osteoporosis preventive behaviors. A literature review was conducted to assess osteoporosis health beliefs, particular those of the health belief model (HBM), such as the perceived susceptibility to osteoporosis, perceived severity of osteoporosis, perceived benefits of osteoporosis preventive behaviors to prevent osteoporosis, perceived barriers to osteoporosis preventive behaviors, and self-efficacy for osteoporosis prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
0
1
0
1
Order By: Relevance
“…Berdasarkan penerapan Health Belief Model (HBM) yang digunakan dalam memprediksi faktor-faktor yang memengaruhi aktivitas fisik untuk mencegah osteoporosis (Nejad et al, 2018). HBM telah digunakan untuk menilai keyakinan terhadap kesehatan terkait osteoporosis dan memprediksi perilaku preventif, seperti aktivitas fisik dan asupan kalsium, guna mengurangi risiko osteoporosis (Nguyen, 2014). Hal ini menekankan pentingnya intervensi perilaku dengan kombinasi program pendidikan kesehatan dalam mempromosikan langkah-langkah pencegahan osteoporosis.…”
Section: Pendahuluanunclassified
“…Berdasarkan penerapan Health Belief Model (HBM) yang digunakan dalam memprediksi faktor-faktor yang memengaruhi aktivitas fisik untuk mencegah osteoporosis (Nejad et al, 2018). HBM telah digunakan untuk menilai keyakinan terhadap kesehatan terkait osteoporosis dan memprediksi perilaku preventif, seperti aktivitas fisik dan asupan kalsium, guna mengurangi risiko osteoporosis (Nguyen, 2014). Hal ini menekankan pentingnya intervensi perilaku dengan kombinasi program pendidikan kesehatan dalam mempromosikan langkah-langkah pencegahan osteoporosis.…”
Section: Pendahuluanunclassified
“…Bronner and Boyington (2002), for example, found that all three studies in their meta-analysis that incorporated Adult Learning principles-based on Knowles' (1984) theory of Andragogy, or adult learning (which posits that adults should be involved with the planning and evaluation of their education) yielded clinically significant weight loss (loss of at least 5% of total body weight) which persisted long after the end of the intervention phase (>12 months). Turning to less commonly-employed theories grounded in pedagogy such as Andragogy may help 47 The health belief model contends that beliefs about health problems, perceived benefits of action and barriers to action, and self-efficacy explain the presence or absence of health-promoting behaviors (Nguyen, 2014). improve the educational elements and subsequent weight loss results of obesity interventions.…”
Section: Theoretical Frameworkmentioning
confidence: 99%